RECURRENT URTICARIA, BLOOD EOSINOPHILIA AND EOSINOPHILIC ASCITES A NEW VARIENT OF GLEICH'S SYNDROME: A New Varient of Gleich’s Syndrome - Dar, Nasser Rashid; Mustafvi, Sajid; Khalique, Khalid; Sharif, Amjad; Majeed, Shahid (Pakistan Armed Forces Medical Journal, 2008)
.